Exemplary Youth Leadership Series: Encourage the Heart - Megan Stein (EDIS, 2021)
This publication series is designed to outline strategies and experiences to expose youth to and engage them with leadership concepts. In this publication, students will try on aspects of the final practice of exemplary leaders: encouraging the heart. Two quick, low-cost activities are included for implementation with youth and adults working with youth. These activities are best suited for students ages 10–18. However, modifications are included for each of the activities to allow for different group sizes, ages, and abilities of the youth participating. This new 2-page publication of the UF/IFAS Department of Agricultural Education and Communication was written by Megan Stein. https://edis.ifas.ufl.edu/wc377